Meta-Interface Analysis for Interaction in Mobile Augmented Reality - Firmanda, Ardiman; Sukaridhoto, Sritrusta; Rante, Hestiasari; Miranto, Cahya; Evianita Dewi Fajrianti; Prasetyaningsih, Sandi (AI Society & STMIK Indonesia, 2022)
Mobile Augmented Reality has expanded including the cultural heritage sector. Among the options offered is the digitization of cultural heritage. Multiple technical breakthroughs has implemented, including hand gesture recognition and body tracking, into mobile augmented reality systems. The success of these improvements depends on a good user interface. Meta User Interface (Meta-UI) allows significant information to be displayed without interfering with system operation. The results of the analyses that the Meta-UI user interface could aid users in employing hand gestures and body motion capture on this mobile augmented reality without any issues and could deliver information about batik efficiently. PIECES Framework testing confirmed this, with a satisfaction score of 4.40 to 4.55. Using the PIECES Framework concepts and questionnaire that focus on user satisfaction with mobile augmented reality, the score indicates that the user is satisfied.